Bronchial rheoplasty for chronic bronchitis: 2-year results from a US feasibility study with RheOx - Victor Kim; Mark T Dransfield; Nathaniel Marchetti; Frank C Sciurba; Alejandro Comellas; Douglas Kyle Hogarth; Adnan Majid (BMJ Open Respiratory Research)
Introduction Chronic bronchitis (CB), a phenotype of chronic obstructive pulmonary disease (COPD) characterised by persistent cough and mucus hypersecretion, is associated with poor outcomes despite guideline-based treatment. Bronchial rheoplasty (BR) with the RheOx system delivers non-thermal pulsed electric fields to the lower airway epithelium and submucosa to reduce mucus producing cells. Early phase clinical trials including 1-year follow-up have demonstrated reduction in airway goblet cell hyperplasia and improvement in CB symptoms.Methods The current multicentre observational BR study enrolled 21 patients with CB at six centres in the USA, with bilateral treatment and 2-year follow-up. Entry criteria included elevated cough and sputum scores from COPD Assessment Test (CAT) and forced expiratory volume in one second<80% predicted. Safety was assessed by serious adverse event (SAE) incidence through 24 months. Clinical utility was evaluated using changes in the CAT, the St. George’s Respiratory Questionnaire (SGRQ) and by comparing exacerbation rates before and following intervention.Results No procedure-related or device-related SAEs occurred. Mean (SD) changes from baseline in CAT at 12 and 24 months were −9.0 (6.7) (p<0.0001) and −5.6 (7.1) (p<0.0047) and in SGRQ were −16.6 (13.2) (p<0.0001) and −11.8 (19.2) (p<0.0227), respectively. There was a 34% reduction in moderate and a 64% reduction in severe COPD exacerbation events compared with the year prior to treatment.Conclusions This study extends the findings from previous feasibility studies, demonstrating that BR can be performed safely and may significantly improve symptoms and health-related quality of life for patients with CB through 24 months.Trail registration number NCT03631472.